PERAN BUZZER MEDIA SOSIAL INSTAGRAM DALAM MEMBENTUK BRAND PRODUK SUSU ALLESGUT (Jurnal Sosial Humaniora dan Pendidikan, 2024)
Social media in the last decade has become a channel that greatly influences all sectors of public life. It allows companies to see what topics are being discussed, what customers want in certain products on social media. The rapid dissemination of product information makes it easy for a brand to be known by Instagram social media users. On Instagram, there are many ways to promote products such as the Instagram Buzzer. The message delivered by buzzers on Instagram is done by combining captions with photos that are interesting and appropriate to the product being promoted. The buzzer's language style is also adapted to each character and is not given specific guidelines or formats. The research entitled "The Role of Instagram Social Media Buzzers in Building the Allesgut Milk Product Brand" used qualitative research methods. This type of research used descriptive research. Descriptive research was used to collect information about the research subject and tried to describe all the circumstances during the research. The results of this research explain that buzzers must meet the category of social media users who already understand the context, the effectiveness of communication, and how to build collaboration and develop connections, in line with the 4C theory. From the perspective of PT. Selaras Husada, buzzers are the right actors on social media who will be able to increase consumer awareness about Allesgut milk products and sales concepts. Buzzers can build awareness of Allesgut milk products among followers.